2010
DOI: 10.1097/qad.0b013e328335cff5
|View full text |Cite
|
Sign up to set email alerts
|

Decline in early life mortality in a high HIV prevalence rural area of South Africa: evidence of HIV prevention or treatment impact?

Abstract: Objective We present early life mortality rates in a largely rural population with high antenatal HIV prevalence, and investigate temporal and spatial associations with a prevention of mother-to-child transmission (PMTCT) programme, an HIV treatment programme, and maternal HIV. Design A retrospective cohort analysis. Methods All births from January 2000 to January 2007 to women in the Africa Centre demographic surveillance were included. Under-two child mortality rates (U2MR) computed as deaths per 1000 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 29 publications
4
54
0
Order By: Relevance
“…Timely initiation of ART in HIV mothers has, however, been shown to reduce under five mortality rates to levels similar to those of children of HIV-negative women 22. A large study in rural South Africa demonstrated that the under 2s mortality rate fell significantly following the initiation of maternal ART—this being the most important contributing factor to the decline in paediatric mortality 23. It is clear, therefore, through the effects of food security and maternal HIV that all children in HIV-positive households are at greater risk of malnutrition than children in households where neither parent has HIV/AIDS.…”
Section: Aetiology Of Disease: Socialmentioning
confidence: 99%
“…Timely initiation of ART in HIV mothers has, however, been shown to reduce under five mortality rates to levels similar to those of children of HIV-negative women 22. A large study in rural South Africa demonstrated that the under 2s mortality rate fell significantly following the initiation of maternal ART—this being the most important contributing factor to the decline in paediatric mortality 23. It is clear, therefore, through the effects of food security and maternal HIV that all children in HIV-positive households are at greater risk of malnutrition than children in households where neither parent has HIV/AIDS.…”
Section: Aetiology Of Disease: Socialmentioning
confidence: 99%
“…1,29 Both the slowing of increases in mortality, also documented subnationally, 24 and the shifting of peak death rates to older ages may be the result of efforts at preventing and treating HIV/AIDS. 24,[30][31][32] The corrected data provide estimates of mortality from HIV/AIDS in South Africa that can complement modelled estimates. For example, the Joint United Nations Programme on HIV/AIDS estimates total deaths from HIV/AIDS in 2006 at 350 000 (range: 300 000-420 000), 33 while the ASSA estimates deaths from HIV/AIDS at about 345 000 in 2006.…”
Section: Misclassified Hiv/aids Deaths In South Africamentioning
confidence: 99%
“…In addition, an increasing number of pregnant women are receiving ART for their own health, reducing HIV transmission to their children and lengthening their lives, thereby reducing mortality among their children (both HIV-positive and HIV-negative) 25. In South Africa, in a largely rural population with a high antenatal HIV prevalence, deaths in infants aged <2 years declined by 49% between 2001 and 2006 26. This was attributed to the availability of PMTCT and ART in public health programmes.…”
Section: Discussionmentioning
confidence: 99%